2012
DOI: 10.1186/1743-8977-9-1
|View full text |Cite
|
Sign up to set email alerts
|

Global gene expression changes in human embryonic lung fibroblasts induced by organic extracts from respirable air particles

Abstract: BackgroundRecently, we used cell-free assays to demonstrate the toxic effects of complex mixtures of organic extracts from urban air particles (PM2.5) collected in four localities of the Czech Republic (Ostrava-Bartovice, Ostrava-Poruba, Karvina and Trebon) which differed in the extent and sources of air pollution. To obtain further insight into the biological mechanisms of action of the extractable organic matter (EOM) from ambient air particles, human embryonic lung fibroblasts (HEL12469) were treated with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
83
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(92 citation statements)
references
References 63 publications
9
83
0
Order By: Relevance
“…In our previous studies, we have focused on comparison of genotoxic dose-responses (determined as DNA adduct formation) with induction of AhR activation in A549 cells [7] and global gene expression in human lung fibroblasts HEL cells treated with the same set of EOM samples [6]. Here, we attempted to identify gene expression changes induced in human alveolar carcinoma A549 cells by a complex mixture of air pollutants adsorbed on PM2.5, and to compare the effects of EOMs originating from distinct localities and sources.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In our previous studies, we have focused on comparison of genotoxic dose-responses (determined as DNA adduct formation) with induction of AhR activation in A549 cells [7] and global gene expression in human lung fibroblasts HEL cells treated with the same set of EOM samples [6]. Here, we attempted to identify gene expression changes induced in human alveolar carcinoma A549 cells by a complex mixture of air pollutants adsorbed on PM2.5, and to compare the effects of EOMs originating from distinct localities and sources.…”
Section: Discussionmentioning
confidence: 99%
“…We recently demonstrated that extractable organic matter (EOM) from these PM2.5 samples induced significant gene expression changes in normal human lung fibroblasts (HEL 12469) [6]. In this study numerous biological processes and signaling pathways have been found to be deregulated in response to various organic extracts from PM2.5, and the key role of the activated AhR has been identified.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…46,47 In human lung fi broblasts, the TGF-b signaling pathway is deregulated in a dose-dependent manner by exposure to extractable organic matter from ambient air pollution. 48 Th is occurs via both up-and downregulation of specifi c genes responsible for TGF-b signaling, highlighting the complex relationship between the exposure and downstream protein activity. Taken together, these data provide biologic plausibility that air pollution could be associated with the development, progression, or exacerbation of ILD via mechanisms of oxidative stress, dysregulated fi brogenesis, and/or infl ammation ( Fig 1 ).…”
Section: Potential Mechanismsmentioning
confidence: 99%